2017
DOI: 10.1111/1754-9485.12623
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the time taken for localised breast surgery pre‐ and post‐introduction of intra‐operative digital specimen mammography

Abstract: We were expecting to confirm a reduction in theatre time with the introduction of IDSM. Surprisingly, no difference in operating times was demonstrated. Factors that influenced the impact of IDSM included the proximity of the imaging department to the operating theatre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…9 , 10 However, previous studies on these outcomes investigating the effects of IDSM have shown inconsistent results. [11][12][13] In this large-cohort retrospective study, we investigated the effect of IDSM implementation on operation time of breast conserving surgery for patients with clinical invasive cancer or ductal carcinoma in situ (DCIS). Additionally, the percentage of cavity shaving on positive margin and re-excision rates is explored .…”
Section: Introductionmentioning
confidence: 99%
“…9 , 10 However, previous studies on these outcomes investigating the effects of IDSM have shown inconsistent results. [11][12][13] In this large-cohort retrospective study, we investigated the effect of IDSM implementation on operation time of breast conserving surgery for patients with clinical invasive cancer or ductal carcinoma in situ (DCIS). Additionally, the percentage of cavity shaving on positive margin and re-excision rates is explored .…”
Section: Introductionmentioning
confidence: 99%